Determinants of the abilities to jump higher and shorten the contact time in a running 1-legged vertical jump in basketball - Miura, K.; Yamamoto, M.; Tamaki, H.; Zushi, K. (The Journal of Strength and Conditioning Research, 2010)
This study was conducted to obtain useful information for developing training techniques for the running 1-legged vertical jump in basketball (lay-up shot jump). The ability to perform the lay-up shot jump and various basic jumps was measured by testing 19 male basketball players. The basic jumps consisted of the 1-legged repeated rebound jump, the 2-legged repeated rebound jump, and the countermovement jump. Jumping height, contact time, and jumping index (jumping height/contact time) were measured and calculated using a contact mat/computer system that recorded the contact and air times. The jumping index indicates power. No significant correlation existed between the jumping height and contact time of the lay-up shot jump, the 2 components of the lay-up shot jump index. As a result, jumping height and contact time were found to be mutually independent abilities. The relationships in contact time between the lay-up shot jump to the 1-legged repeated rebound jump and the 2-legged repeated rebound jump were correlated on the same significance levels (p < 0.05). A significant correlation for jumping height existed between the 1-legged repeated rebound jump and the lay-up shot jump (p < 0.05), although none existed for jumping height between the lay-up shot jump and both the 2-legged repeated rebound jump and countermovement jump. The lay-up shot index correlated more strongly to the 1-legged repeated rebound jump index (p < 0.01) when compared to the 2-legged repeated rebound jump index (p < 0.05). These results suggest that the 1-legged repeated rebound jump is effective in improving both contact time and jumping height in the lay-up shot jump.